Identification of common genetic variants associated with serum concentrations of p, p′-DDE in non-occupational populations in eastern China. (July 2021) - Li, Shushu; Shao, Wei; Wang, Chao; Wang, Li; Xia, Rong; Yao, Shen; Du, Mulong; Ji, Xiaoming; Chu, Haiyan; Zhang, Zhengdong; Wang, Meilin; Wang, Shou-Lin
Graphical abstract: Highlights: rs3181842 or rs2279345 is novel loci in CYP2B6 related to low human serum p, p ′ - DDE. rs3181842 or rs2279345 resulted in poor capacity of CYP2B6 in p, p ′ - DDT metabolism. Genetics is more responsible for interindividual exposure differences than environment. Genetic variants related to human internal exposure of DDT/DDE are explored by GWAS. EDI can well adjust the interference of environmental exposure to DDT/DDE in human. Abstract: Dichlorodiphenyldichloroethylene (DDE) is the major and most stable toxic metabolite of dichlorodiphenyltrichloroethane (DDT), a well-known organochlorine pesticide banned worldwide in the 1980s. However, it remains easy to detect in humans, and internal levels vary widely among individuals. In the present study, a genome-wide association study (GWAS) (511 subjects) and two replications (812 and 1030 subjects) were performed in non-occupational populations in eastern China. An estimated dietary intake (EDI) of p, p ′ - DDT and p, p ′ - DDE was calculated by a food frequency questionnaire (FFQ) and the determination of 195 food and 85 drinking water samples. In addition, functional verifications of susceptible loci were performed by dual-luciferase reporter, immunoblotting and metabolic activity assays in vitro . p, p ′ - DDT and p, p ′ - DDE were measured using gas chromatography-tandem mass spectrometry (GC-MS/MS). A common loci rs3181842 (high linkage equilibrium with rs2279345) in CYP2B6 at 19p13.2 were found to be strongly associated with low serum levels of p, p ′ - DDE in this population in GWAS and were verified by two replications and combined analysis of 2353 subjects ( P = 1.00 × 10 -22 ). In addition, p, p ′ - DDE levels were significantly lower in subjects with the rs3181842 C allele than in those carrying the normal genotype, even in individuals with similar EDIs of p, p ′-DDT. Furthermore, the rs3181842 C allele functionally led to low CYP2B6 expression and activity, resulting in a low metabolic capacity for the formation of p, p ′ - DDE from p, p ′ - DDT. The study highlighted that CYP2B6 variants were more relevant than environmental exposure to internal p, p ′-DDE exposure, which is important information for DDT risk assessments.